Investment Implications of Information Acquisition and Leakage - Dye, Ronald A.; Sridhar, Sri S. (Management Science, 2003)
This paper studies when a firm will acquire additional information about a potential new project by consulting outsiders, when doing so runs the risk of reducing the value of implementing the project as a consequence of information leakage. The analysis evaluates the firm's information acquisition activities in both the presence and absence of moral hazard in project production.